Computational design of functional random heteropolymers through atomistic simulations - Tianyi Jin; Collin S. Lung; Ting Xu; Connor W. Coley; Alfredo Alexander-Katz (PLoS ONE, 2026)
Random heteropolymers (RHPs) are emerging single-chain nanoparticles with great potential in protein mimicry, yet a systematic understanding of how chemical composition and monomer structures govern their structure, dynamics, and hydration remains limited. Using atomistic molecular dynamics simulations, we examine how various design parameters, including chain length, backbone architecture, charged monomer concentration, chain-level composition, and side-chain micropolarity influence RHP assembly and hydration behavior. As chain length increases, methacrylate-based RHPs transition from rod-like to random-walk statistics and ultimately collapse into compact globules stabilized by hydrophobic collapse and methacrylate-poly(ethylene glycol) (PEG) interactions. Positively charged monomers follow the Hofmeister series in their hydration. Interestingly, the dimerization results from hydrophobic and PEG-positively charged-monomer interactions, and not from opposite charge interactions. Alternative backbones such as acrylate and (meth)acrylamide display sequence-dependent compactness and dynamics, reflecting greater chemical sensitivity. PEG side-chain length strongly affects solubility and hydration, with shorter side chains making the overall chain more hydrophobic. Also, we show that branching-induced micropolarity modulates local hydration patterns of hydrophobic residues. Overall, these results establish general molecular design principles for tuning the assembly and dynamics of RHPs through compositional and chemical control, providing a foundation for engineering synthetic polymers that mimic the compactness, hydration, and functional adaptability of proteins.